Mapping the Digital Shift: A Bibliometric Analysis of Post-Pandemic Consumer Behavior in ASEAN (2020–2025) - Bartenputri, Ameliasari; Wardi, Yunia; Evanita, Susi (Universitas Muhammadiyah Pontianak, 2026)
This bibliometric analysis maps post-pandemic consumer behavior research in ASEAN (2020–2025) using 42 Scopus-indexed articles. Tools like VOSviewer and Biblioshiny reveal trends, key themes (e.g., “COVID-19,” “e-commerce”), and regional focus (e.g., Indonesia, Vietnam). Universiti Teknologi MARA leads in output. Co-citation networks highlight the Theory of Planned Behavior and PLS-SEM, while co-authorship remains fragmented. The study uncovers digital, geographical, and behavioral dimensions, signaling a shift toward online consumption driven by health risks and tech adoption. Findings offer insights for future research, policymaking, and industry strategies in navigating ASEAN’s evolving consumer landscape.